Undergraduate Teaching of Art History in a Studio Context - Abdullah, Sarena (NUS Press, 2020)
At Universiti Sains Malaysia (USM), art history papers are offered as core papers to Fine Arts students at the School of the Arts. Thus, I have developed Art History courses for Fine Arts, rather than Art History students. This required me to re-strategize the approach and learning outcomes of my classes to suit the needs of studio major students. Most of these Fine Arts students are accepted based on their Form Six Sijil Tinggi Persekolahan Malaysia (STPM) results or diploma certificates. Besides their academic qualifications, they are screened by way of a drawing assessment and an interview process. Thus, developing art history pedagogy subjects for Fine Arts students required further consideration of whether their backgrounds and interests are based on studio rather than art history. Every year, around 30 students